Pemodelan Kehilangan Tekanan pada Sumur Dominasi Air Case Study - Nur Rochman, Ebbryl
This study discusses the modelling off pressure drop in flow pipe. Pressure drop modeling is a type of well modeling that benefits for feed zone characterization, transient analysis, decline curve and identification of well problems such as scaling. The models must be very precise to ensure a good design. Therefore, analytical simulator is made which contains various types of bubble flow, slug flow, transition and mist flow. This analytical simulator was made to calculate the pressure drop from the bottom of the well to the surface. The correlation of pressure drops made there are 8 including Beggs-Brill, Harr-Frees, Lock-Mart, Duns-Ros, Hage-Brown, Aziz et al., Orkizewski, and Chierici et al. provided in the simulator. Then for case studies, data from two phase water dominated geothermal well is used as validation. This study focuses on the development of new analytical simulators from Geothermal ITB Simulator with the addition of correlations, namely Aziz et al, which is a mechanistic method by making changes to the flow pattern map, Orkizewski correlation which combines correlations and modifies them, and Chierici et al. correlation who tried to change the calculation on the Slug flow type on Orkizewski. This study found a result that the method of Aziz et al. has the highest accuracy with 8% error for case studies on water dominated fields.